Too Much Creativity? The Traps of Everyday and Amateur Creativity in the Culture of Excess, Kitch and Insipidness - Szmidt, Krzysztof J. (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The article is devoted to the problem of the excess of the products of creative activities, especially the everyday and amateur ones, which we come across on digital platforms or in media. The author describes the symptoms of this excess, referring to the critical analysis of culture sociologists, and he puts forward a hypothesis that the influx of the creativity is partly caused by many everyday artists and amateurs falling into three main traps, namely the trap of the illusion of the easiness of the creative procces, the trap of the disappearance of tools for a reliable selection of the creations and the trap of the over easiness of communicating the products of creativity. After unmasking the mechanisms of these ?traps? there comes an attempt to outline a positive educational programme, based on the concept of A. Ericsson?s deepened exercises and ?the principle of 10 years?, which are the conditions of climbing the ladder of professional and master?s creativity.